Numerical Approximation of an Axisymmetric Elastoacoustic Eigenvalue Problem (Communications in Computational Physics, 2023)
This paper deals with the numerical approximation of a pressure/displacement formulation of the elastoacoustic vibration problem in the axisymmetric case.We propose and analyze a discretization based on Lagrangian finite elements in thefluid and solid domains. We show that the scheme provides a correct approximationof the spectrum and prove quasi-optimal error estimates. We report numerical resultsto validate the proposed methodology for elastoacoustic vibrations.
Keywords: Axisymmetric problem; fluid-structure interaction; spectral problem; finite element method.